Nestin expression by newly formed human blood vessels - Mokrý, J; Cízková, D; Filip, S; Ehrmann, J; Osterreicher, J; Kolár, Z; English, D (Stem cells and development, 2004)
Nestin is a type VI intermediate filament protein originally described in neural stem cells. Here we report that immature endothelial cells generated in the course of angiogenesis express nestin. Endothelial cells of embryonic capillaries destined to vascularize growing organs also express this intermediate filament protein. Whereas nestin was sporadically expressed in mature adult human endothelial cells sporadically express nestin, this protein was consistently expressed in adult angiogenic vasculature. Nestin expression was also detected in capillaries of the corpus luteum, which replenishes itself by angiogenesis. Nestin-immunoreactive vessels were also observed in the infarcted hearts where transient ischemia triggered regeneration accompanied with neovascularization of the myocardium. Nestinpositive endothelial cells lined vessels nourishing solid growing tumors, including melanoblastomas and glioblastomas. Our data provide definitive evidence that endothelial precursors express the neural stem cell marker nestin and that this protein participates in formation of the cytoskeleton of newly formed endothelial cells. Because nestin expression was recognized under all conditions of vascular development, nestin represents a novel and reliable marker of neovascularization.
Keywords: Neurons; Up-Regulation; Cell Differentiation; Glioblastoma; Endothelium, Vascular; upregulace; imunohistochemie; Melanocytes; infarkt myokardu; Neovascularization, Physiologic; Nestin; glioblastom; fyziologická neovaskularizace; Nerve Tissue Proteins; Myocardial Infarction; Corpus Luteum; cévy; Immunohistochemistry; ženské pohlaví; corpus luteum; myokard; Humans; Myocardium; Intermediate Filament Proteins; proteiny nervové tkáně; neurony; cévní endotel; Stem Cells; buněčná diferenciace; kmenové buňky; proteiny intermediálních filament; Female; nestin; Blood Vessels; lidé; melanocyty